2021
DOI: 10.1016/j.ijcard.2021.07.042
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA HCP5 in hBMSC-derived exosomes alleviates myocardial ischemia reperfusion injury by sponging miR-497 to activate IGF1/PI3K/AKT pathway

Abstract: Ischemia/reperfusion (I/R) injury is an inevitable process during heart transplant and suppressing I/R injury could greatly improve the survival rate of recipients. Mesenchymal stem cells (MSCs) have positive effects on I/R. We aimed to investigate the mechanisms underlying the protective roles of MSCs in I/R. Both cell model and rat model of myocardial I/R were used. MTT assay and flow cytometry were used to measure cell viability and apoptosis, respectively. QRT-PCR and western blotting were employed to meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 36 publications
1
36
0
Order By: Relevance
“…According to the abundance of the genes, IFG1 was identified as a target of mmu-miR-27b-3p. The study has indicated that IFG1 can reduce MI/R injury via activating the PI3K/AKT pathway [ 29 ]. Moreover, Chen et al indicated that upregulated miR-27b-3p could inhibit the progression of breast cancer via targeting the PI3K/AKT pathway [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the abundance of the genes, IFG1 was identified as a target of mmu-miR-27b-3p. The study has indicated that IFG1 can reduce MI/R injury via activating the PI3K/AKT pathway [ 29 ]. Moreover, Chen et al indicated that upregulated miR-27b-3p could inhibit the progression of breast cancer via targeting the PI3K/AKT pathway [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Long noncoding RNAs (lncRNAs) have been involved in the apoptosis, 24 proliferation or regeneration of cardiomyocyte. [25][26][27] Moreover, lncRNAs in exosomes have been shown to be involved in the inhibition of cardiomyocyte apoptosis 28,29 and pyroptosis. 30 In this study, we constructed DIC model in vitro firstly.…”
Section: Introductionmentioning
confidence: 99%
“…An increase of miR-497 during ischemia-reperfusion (I/R) injury may cause cardiomyocyte apoptosis. Li et al ( Li K.-S. et al, 2021 ) confirmed that Introducing Exo-lncRNA-HCP5 in hBMSCs into cardiomyocytes can protect cardiomyocytes from injury via the miR-497↓/insulin like growth factor-1 (IGF-1)/phosphatidylinositide 3-kinases (PI3K)/protein kinase B (AKT)↓ signal pathway. Meanwhile, Zhang et al ( Zhang J.-K. et al, 2022 ) treated HL-1 mouse cardiomyocytes and myocardial tissue of hypoxia reperfusion (H/R) myocardial cells ferroptosis mouse model with BMSCs-Exo-lncRNA-Mir9-3hg.…”
Section: Ascs-exo-lncrnas With Diverse Organ Sourcesmentioning
confidence: 99%